Notary's Responsibility in Making Authentic Deeds Containing False Statements by The Parties with Much Knowledge - Radiansyah, Radiansyah; Sulchan, Achmad (TABELLIUS: Journal of Law, 2025)
Abstract. In practice, there are still many Notaries who do not comply with these regulations, thus causing losses to the public (their clients) who seek legal justice in making an agreement or notarial deed. The purpose of this study is to determine the unlawful acts committed by Notaries in making authentic deeds with false information by the parties known together and the notary's responsibility for their actions in violation of criminal law and the Notary's code of ethics. This study uses a normative juridical approach, through a statutory approach (statute approach). The types and sources of data in this study use secondary data obtained from literature studies and the analysis in this study is prescriptive. Based on this study, it is concluded that Notaries who make authentic deeds with false information by the parties known together are unlawful acts and can be categorized as committing a criminal act and also a violation of the Notary's Office. These actions can be subject to criminal sanctions in accordance with the Criminal Code (KUHP) and administrative sanctions in accordance with the UUJN and the Notary's Code of Ethics. In this research, it was found that a Notary was sentenced by the Panel of Judges at the District Court for unlawful acts in making authentic deeds with false statements by the parties.Which It is the responsibility of the Notary who collaborates with other parties to make an authentic deed with false information, so that he must undergo criminal or punishment after a court decision that has permanent legal force, because the Notary's unlawful actions have fulfilled the elements of the articles in the Public Prosecutor's indictment and mutually accept the decision without making an appeal. Keywords: Authentic Deed; False Statement; Notary; Unlawful.